Prenatal Mercuric Chloride Exposure Causes Developmental Deficits in Rat Cortex - Tayebeh Rastegar; Kazem Parivar; Maliheh Nobakht; Ali Shahbazi; Siamak Alizadeh Zendehrood; Mehdi Mehdizadeh (Basic and Clinical Neuroscience, 2011)
Introduction: Environmental pollution with heavy metals such as mercury is a major health problem. Growing studies on the field have shown the deleterious effects of mercury on human and nonhuman nervous system, especially in infants, however the effects of prenatal exposure to mercuricchloride on cortical development are not yet well understood. The aim of this study was to investigate the effect of prenatal exposure to mercuric chloride on morphological characteristics of brain cortex. Methods: Mercuric chloride (2 mg/kg) or normal saline were injected (I.P.) to 36 Sprague – dawley rats in the 8th, 9th or 10th day of gestation. The embryos were surgically removed in the 15th day of gestation, and brain cortices were studied by histological techniques. Results: Histological studies showed that embryos of mercuric chloride treated rats hadcortical neuronal disarrangement withdifferent orientations of nuclei, increased diameter of cortex, increased mitosis of cells, increased cell death, decreased cellular density and increased intracellular space. Conclusion: These findings suggest some micro structural abnormalities in cortical regions after prenatal exposure to mercuric chloride. These structural abnormalities may underliesome neurologic disturbances following mercury intoxication.